2018
DOI: 10.1111/tid.12950
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant liver graft schistosomiasis in a migrant from Sub‐Saharan Africa

Abstract: We report a case of post-transplant liver graft infection with Schistosoma spp in a migrant from sub-Saharan Africa transplanted for HBV-related cirrhosis and with undiagnosed schistosomiasis pre-transplantation. The occurrence of tropical diseases in non-endemic areas warrants screening protocols for organ donors and recipients with a history of exposure in endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Abnormal liver enzyme levels were only transiently detected in three patients, demonstrating an active granulomatous reaction and S.mansoni eggs 25 , 26 . In two recipients and one infected graft, morbidity caused by parasitic infection was suspected but not confirmed 31 , 33 , 38 . For the two infected recipients, late-stage epithelioid and fibrotic granulomas, and eggs were detected in follow-up biopsies performed 8 months and 11 years after surgery, respectively; however, organ dysfunction was not detected 31 , 38 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Abnormal liver enzyme levels were only transiently detected in three patients, demonstrating an active granulomatous reaction and S.mansoni eggs 25 , 26 . In two recipients and one infected graft, morbidity caused by parasitic infection was suspected but not confirmed 31 , 33 , 38 . For the two infected recipients, late-stage epithelioid and fibrotic granulomas, and eggs were detected in follow-up biopsies performed 8 months and 11 years after surgery, respectively; however, organ dysfunction was not detected 31 , 38 .…”
Section: Resultsmentioning
confidence: 92%
“…In two recipients and one infected graft, morbidity caused by parasitic infection was suspected but not confirmed 31 , 33 , 38 . For the two infected recipients, late-stage epithelioid and fibrotic granulomas, and eggs were detected in follow-up biopsies performed 8 months and 11 years after surgery, respectively; however, organ dysfunction was not detected 31 , 38 . Regarding infected grafts, Vincenzi et al 33 did not rule out the possibility that schistosomiasis contributed to graft loss in their series of six LTs.…”
Section: Resultsmentioning
confidence: 92%
“…In the literature, reported cases of schistosomiasis after liver transplantation, in patients with different underlying diseases, showed graft recovery after the use of praziquantel 8 - 11 . In the cases reported herein, attention is drawn to the significant increase in serum liver tests, occurring over a period of two to eighteen months after transplantation, both requiring liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Schistosoma after solid organ transplantation is most studied in renal graft recipients, and the first cases of schistosomiasis in liver grafts were published in the 2000s. Since then, authors have discussed the pathogenesis and progression of the disease after liver transplantation 8 - 11 . In light of what has been published previously, there is no reason to believe that S. mansoni eggs in a liver graft will end up infecting the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some parasi-tes (Cryptosporidium, Cyclospora, Entamoeba histolytica, Toxoplasma and Giardia) acquired from the donor allograft, from reactivation, or from de novo acquisition posttransplantation (Cooper et al, 2017). Carrai et al (2018) in the United Kingdom reported a case of post-transplant liver graft infection with Schistosoma spp. in a migrant from the Sub-Saharan Africa transplanted for HBVrelated cirrhosis and with undiagnosed schistosomiasis pre-transplantation.…”
Section: Introductionmentioning
confidence: 99%